Pengaruh Current Ratio, Return on Asset, Dan Debt to Equity Ratio Terhadap Harga Saham Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2024 - Javirah Dhenita; Yani Suryani; Liza Novietta (Journal of Innovative and Creativity, 2025)
This study aims to determine the effect of the Current Ratio, Return on Assets, and Debt to Equity Ratio on stock prices, with dividend policy as an intervening variable, in manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2024. The sample selection method used was purposive sampling. A total of 217 observations were made over 7 years, spanning 31 companies. The data analysis technique used in this study was path analysis. The results of the Substructure I test indicate that the Debt to Equity Ratio has a positive effect on dividend policy. In contrast, the Current Ratio and Return on Assets do not affect dividend policy. The results of the Substructure II test indicate that the Current Ratio and Return on Assets have a positive effect on stock prices. In contrast, the Debt to Equity Ratio and dividend policy do not affect stock prices. The Sobel test results indicate that dividend policy is able to mediate the effect of the Debt to Equity Ratio on stock prices. In contrast, dividend policy is unable to mediate the effect of the Current Ratio and Return on Assets on stock prices.